Meadow katydids (Orthoptera: Tettigoniidae: Conocephalini) from the Central-West Region of Brazil: Morphological, bioacoustic and cytogenetic study - Chamorro-Rengifo, Juliana; Silva, Bruno Cansanção; Olivier, Renan Da Silva; Braun, Holger; Araujo, Douglas (Zootaxa, 2018)
Three species of Conocephalus and two of Euxiphidion from several localities of the Central-West Region of Brazil were studied. Conocephalus goianus Piza, 1977, C. saltator (Saussure, 1859) and C. versicolor (Redtenbacher, 1891) are recorded for the first time from Mato Grosso do Sul, one new species Euxiphidion veroni sp. nov. is described, and a new combination, Euxiphidion caizanum comb. nov. is proposed. The calling songs of C. saltator, C. versicolor, and E. veroni sp. nov. are described. All these three species call very continuously, also in the daytime. The three species of Conocepha-lus have mitotic metaphases with 2n♂ = 33 = 32 + X and 2n♀ = 34 = 32 + XX. Euxiphidion caizanum comb. nov. and    E. veroni sp. nov. have 2n♂ = 31 = 30 + X and 2n♀ = 32 = 30 + XX. Most of the autosomes of C. saltator and C. versicolor are meta/submetacentric, differing from C. goianus that has seven biarmed and nine monoarmed autosomes. Both Euxiphidion species present mostly telo/subtelocentric autosomes. The X chromosome is metacentric, and the largest element of the karyotype in the five species. No interstitial telomeric site (ITS) was observed in mitotic metaphases submitted to telomeric fluorescent in situ hybridization. Ecological aspects of the studied species are discussed.